CRISPR/Cas9 editing in conditionally immortalized HoxB8 cells for studying gene regulation in mouse dendritic cells. Issue 11 (19th December 2021) - Xu, Huaming; Look, Thomas; Prithiviraj, Sujeethkumar; Lennartz, Daniel; Cáceres, Manuel Delgado; Götz, Katrin; Wanek, Paul; Häcker, Hans; Kramann, Rafael; Seré, Kristin; Zenke, Martin
Abstract : HoxB8 multipotent progenitors (MPP) are obtained by expression of the estrogen receptor hormone binding domain (ERHBD) HoxB8 fusion gene in mouse BM cells. HoxB8 MPP generate (i) the full complement of DC subsets (cDC1, cDC2, and pDC) in vitro and in vivo and (ii) allow CRISPR/Cas9‐mediated gene editing, for example, generating homozygous deletions in cis‐acting DNA elements at high precision, and (iii) efficient gene repression by dCas9‐KRAB for studying gene regulation in DC differentiation.